Grafika Mengabdi dan Menginspirasi: Pelatihan Kalkulasi Biaya Produksi Cetak di SMKN 7 Jakarta: Service and Inspiring Graphics: Print Production Cost Calculation Training at SMKN 7 Jakarta - Yessy Yerta Situngkir; Mawan Nugraha; Susiani Susiani; Antinah Latif (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
One of the essential resources in management is human resources. The importance of human resources needs to be realized by all levels of management. Schools as a unified education system are expected to provide learning experiences for all students to master competencies by the level of education and the unique mission it carries. However, the lack of human resources allows this service movement to fill the existing problems. The training carried out is the calculation of print production costs. In implementing this community service activity, several methods are used, including observation, interviews, discussions, questionnaires, theory, and practice calculating the cost of print production and ending with an evaluation. There was an increase in students' knowledge from 10% to 83.33% after the training. Suppose the school has difficulty finding teachers/HR according to their competence in teaching print cost calculation subjects. In that case, the school should often provide training from higher education institutions and industry to reduce HR competencies gaps.